Physicochemical and Organoleptic Characteristics of Cookies Made from Mocaf and Purple Sweet Potato Flour with The Addition of Robusta Coffee Powder - Oktaviani Oktaviani; Muhammad Handika Wahyu Agung Nugraha (Jurnal Ilmu Pertanian Indonesia, 2025)
Proximate analysis was conducted on cookies with different formulations of mocaf, purple sweet potato flour, and robusta coffee powder. This study aimed to analyze the proximate composition of cookies containing mocaf, purple sweet potato flour, and robusta coffee powder. A completely randomized design with five different treatments was used. The results showed that the moisture content ranged from 5.42% to 6.43%, with A5 (25% mocaf + 50% purple sweet potato flour + 5% robusta coffee powder) having the highest moisture level, exceeding the SNI standard (≤5%). The ash content ranged from 0.96% to 1.47%, meeting the SNI standard (≤1.5%). The highest fat content was found in A5 (35.03%) and A4 (50% mocaf + 50% purple sweet potato flour + 5% robusta coffee powder, 33.44%), which exceeded the SNI standard (≤9%). The highest protein content was also found in A5 (4.42%) but remained below the SNI standard (≥5%). The highest carbohydrate content was found in A1 (60.88%), whereas A5 had the lowest (52.79%). The highest crude fiber content was obtained for A5 (7.32%). The study concluded that increasing the proportion of purple sweet potato flour increased moisture, ash, fat, protein, and crude fiber content but decreased carbohydrate levels. In contrast, a higher proportion of mocaf increased carbohydrate content but reduced crude fiber levels. Keywords: proximate analysis, robusta coffee powder, cookies, mocaf, purple sweet potato flour